Outcomes of newborns screened for congenital hypothyroidism in Turkey - a single center experience - Esen, Ihsan; Eraslan, Nilgun; Okdemir, Deniz (Walter de Gruyter Gmbh, 2025)
Objectives: It was aimed to investigate the outcomes of babies referred to a tertiary health center in Turkey for evaluation primary congenital hypothyroidism (CH) through newborn screening. Methods: The hospital files of 328 newborns who were referred for CH from newborn screening between June 2013 and June 2020 were retrospectively reviewed. The newborns were evaluated with their clinical characteristics at admission, as well as their follow-up data and final diagnoses. Results: Sixteen (4.9 %) newborns were diagnosed with transient neonatal hyperthyrotropinemia after follow-up. Treatment was initiated in 166 (50.6 %) of the cases with a diagnosis of CH. The median age at initiation of treatment was 17 days (5-69). Treatment was initiated in 88.3 % of the cases in the first month of the life. After at least 3 years of follow-up, 30/120 (20.0 %) of the cases were diagnosed with permanent CH and 11/30 (36.7 %) of them were diagnosed with thyroid dysgenesis. All of the cases who used >37.5 mu g per day levothyroxine at the age of 1 or 2 years were diagnosed with permanent CH during their follow-up. For the prediction of transient CH, the sensitivity and specificity of levothyroxine doses of <= 25 mu g per day at 1 year of age were calculated as 96.2 and 46.2 %, and for 2 years of age, the sensitivity and specificity were calculated as 97.8 and 65.2 %. Conclusions: In this cohort, 10 % of all referrals result in permanent CH. Thyroid imaging with ultrasonography and levothyroxine dose during follow-up can be guiding in predicting permanent CH.
Keywords: congenital hypothyroidism; newborn screening; thyroid dysgenesis